Actividad física recreativa en el adulto mayor (2015)
ABSTRACT: Nowadays, the increase in longevity is one of the current concerns in the world. Therefore, to generate evaluative research related to quality of life in the elderly is a necessity. The Active Life in the Elderly Program through recreation, addressed to 19 participants belonging to the neighborhood called Panorama, in Manizales city, attempted first to assess body composition (height, weight, waist circumference and skinfolds), fitness (flexibility, static balance, endurance and strength, Senior Fitness Test Battery) and quality of life of the elderly (tab “WHOQOL-100”); second, to design and implement the program based on the results obtained before; and third, to evaluate the teacher’s role and the importance of the said program (openquestions survey). Methodology: This research is basically a quantitative study, with a descriptive-evaluative design and a mixed approach. It uses pre- and post-test techniques. Qualitatively, it is based on the Evaluative Research. Results: The implementation of the program helped elderly participants reduce body weight and improve their physical condition. Additionally, recreation with educational sense improved elderly quality of life.